2001
DOI: 10.1074/jbc.m103954200
|View full text |Cite
|
Sign up to set email alerts
|

The Low Density Lipoprotein Receptor-related Protein Contributes to Selective Uptake of High Density Lipoprotein Cholesteryl Esters by SW872 Liposarcoma Cells and Primary Human Adipocytes

Abstract: The concept that selective transfer of high density lipoprotein (HDL)-derived cholesteryl esters (CE) does not require lipoprotein internalization has been challenged recently by evidence that implicates HDL recycling during the selective uptake process. This has prompted us to examine the role of the low density lipoprotein receptor-related protein (LRP) in selective uptake. LRP is an endocytic receptor for lipoprotein lipase (LpL) and apolipoprotein E (apoE) ligands that are able to mediate selective uptake.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 60 publications
2
62
1
2
Order By: Relevance
“…Lactoferrin has previously been described to inhibit the selective uptake of HDL cholesteryl esters by 35%-50% in human primary adipocytes and SW872 liposarcoma cells (22 ). This action is mediated via interaction with LRP, which contributes physiologically to the selective uptake of HDL cholesteryl ester in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Lactoferrin has previously been described to inhibit the selective uptake of HDL cholesteryl esters by 35%-50% in human primary adipocytes and SW872 liposarcoma cells (22 ). This action is mediated via interaction with LRP, which contributes physiologically to the selective uptake of HDL cholesteryl ester in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Also in mice with a targeted deletion of the LDL-receptor gene, the up-regulation of selective CEuptake suggests that SR-BI can compensate for the loss of LDL-receptor function [58]. Recently, the LDL-receptor related protein has also been addressed to mediate, at least in part, selective lipid uptake [59]. LDL-receptor related protein was found to be associated with syncytiotrophoblasts (but not cytotrophoblasts) and BeWo cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that specific mammalian tissues may selectively take up lipoprotein-bound components with LDLR homologous receptors (e.g. LRP), however, without endocytosis of the ligand (Vassiliou et al, 2001;Swarnakar et al, 2001). Additionally, alternative functions for LDLR that deviate from the classic lysosomal lipoprotein delivery could also depend on the developmental stage or type of tissue (Dehouck et al, 1997).…”
Section: Discussionmentioning
confidence: 99%